Study on the Optimization of Process Conditions for the Development of Purple Rice Milk Product: https://doi.org/10.69692/SUJMRD0802100 - BANYAVONGSA, Anna; THIKEO, Satheun; SIBOUNNAVONG, Phonesavard; KEOMIXAY, Phoukham; KEOMANY, Daosavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study was to study the development of purple rice milk products, which aimed 1) to study on the optimization for digestion of starch using Amylase enzymes and 2) to evaluate the sensory of rice milk products. In the experiment designed of the optimization was used two factors include time with 35, 40, 45, 50 mintue and enzymes concentation 0.05%, 0.1%, 0.15% and 0.2% and using CCD (Central Composite Design) and RSM (Response Surface Methodology) were investigated the optimum condition which results in the analysis of two factors with duration of hydrolysis was 43 minute and concentration of enzymes was 0.141% consisted high value of total soluble solid (TTS) 10.33 and SD value of 0.57 with R2 85.152%. For the sensory evaluation was used QDA (Quantitative Descriptive Analysis) method, which is an evaluation of the characteristics of the product from the tester. The formulation of rice milk was divided into 5 formulas. In determining the specific characteristics of the product was set at 16 specify Characterized by the main characteristics include: odor, taste, texture and after tasting. The sensory evaluation results showed that: Formula 2 consisted of rice odor, sugar odor, caramel odor, sweet, soft, liquid, tasted in the mouth and refreshing. Formula 4 consisted of a pungent, sugary, aromatic, caramel, sweet, soft, liquid, mouth-watering and refreshing taste, and The results of the analysis was used PCA which analyzed priciple component (PC) with a confidence level of 85.57%. As for the preference percentage of the product obtained from Preferance mapping analysis the result be seen that the preference percentage of all 5 formulations were as follows: Formula 2 rice 50% with soybean 50% and formula 4 rice 50% with peanut 50% accouting for 60%-80%, After analyzing the data to find the difference, it was found that the raw materials used in purple rice milk in formulas 2, 3, 4 and 5 consisted of purple rice, soybeans, sesame seeds and peanuts were significantly affect to charateristic and preferance of the products